Planejamento e gestão ambiental no distrito industrial de João Pessoa-PB: análise crítica. - Rodrigues, Caio Marcelo Sampaio (2012)
This study has in its fundamental scope the objective to analyze critically of the acts of public authorities in environmental planning and managing in the main industrial district (ID) at the city of João Pessoa/PB. The rescue of the historical, economical industrial processes occurring in Brazil, at Northeast Region and at Paraíba, along with the implementation of ID showed the origin of developmental choices, which boosted the industrial growth of the study area. The field investigations supported by the Civil Public Investigation 030/2007 of the Environmental Prosecutor of the capital of the State of Paraíba performed in 58 industries in the universe of 118 (CINEP, 2011) between the years 2009 and 2010 exposed the following of each industrial enterprise: licensing; water grants, use and occupation; industrial and sanitary wastewater, treatment and disposal, water supply, solid waste, type and final destination. Environmental legislation has been used as a parameter to assess how far the reality was contained in the environmental standards. We analyzed the presence and actions in each state factor of environmental planning and managing of the ID, assessing what were the goals of environmental agencies, its history, its importance and what was their performance at the facts found. The results were compared with the parameters determined in the local, state and federal environmental legislation, showed that the negative impacts caused by industrial activities in all aspects evaluated are proportional to the insignificant role of public administration. Despite the entire environment legislative development, and also technologies less harmful to the environment and especially to the man, the search for a better quality of life for the people, the government prioritizes yet, only the factors directly linked to economic growth contributing decisively to accentuate the imbalance between industrial activities, the environment, and consequently, human.